A survey on privacy preserving and content protecting location based queries - Praveen Kumar, K.; Anitha, M. (International Journal of Engineering and Technology, 2017)
This paper presents a solution to one of the situation-based totally question problems. This downside is printed as follows: (i) a user desires to question a data of area records, referred to as factors Of interest (POI), and doesn't want to reveal his/her vicinity to the server way to privacy concerns; (ii) the proprietor of the state of affairs data, that is, the place server, would not wish to effortlessly distribute its statistics to any or all users. The scenario server needs to personal a few control over its data, since the data is its fine. A location based question resolution that employs 2 protocols that allows a person to privately verify and acquire vicinity statistics. The primary step is for a consumer to in private verify his/her region victimization oblivious switch on a public grid. Oblivious switch accustomed supply the goods a more secure resolution for every parties. the second one step involves a personal information retrieval interplay that retrieves the report with high communication performance. the answer this is gift is economical and realistic in numerous conditions. This paper consists of the effects of a operating example as an example the potency of our protocol.